1998
DOI: 10.1038/sj.gt.3300715
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in vitro and in vivo gene delivery using cationic agent complexed retrovirus vectors

Abstract: Retroviruses are, at present, the most efficient integrative mediated infection without cytotoxicity. To increase virus vectors available for gene delivery. However, these viruses infectivity further we combined the enhancing effect of are still limited by relatively low titres. Although several pro-DOGS on virus infectivity with concentration of virus partocols exist to improve virus titre most of them are timeticles by ultrafiltration to reach titres of 1 × 10 9 IU/ml. The consuming and unable to provide suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 16 publications
3
35
1
Order By: Relevance
“…Indeed, when polybrene 4 ug/ml and DOGS 2 ug/ml were microinjected into rat testes, and the testes were histologically analyzed after 2-5 months, DOGS-treated group displayed spermatogenesis in the seminiferous tubules of more than 80% of the recipients while in the polybrene-treated groups showed spermatogenesis in only 20% of the recipients (unpublished data). Themis and Forbes (1998) performed internal transduction by injecting retrovirus directly into the body, and showed efficient transduction into tissue cells can be achieved by the addition of DOGS. Similarly our results for this study showed lower cytotoxicity for the DOGS-treated group compared with the polybrene-treated group (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when polybrene 4 ug/ml and DOGS 2 ug/ml were microinjected into rat testes, and the testes were histologically analyzed after 2-5 months, DOGS-treated group displayed spermatogenesis in the seminiferous tubules of more than 80% of the recipients while in the polybrene-treated groups showed spermatogenesis in only 20% of the recipients (unpublished data). Themis and Forbes (1998) performed internal transduction by injecting retrovirus directly into the body, and showed efficient transduction into tissue cells can be achieved by the addition of DOGS. Similarly our results for this study showed lower cytotoxicity for the DOGS-treated group compared with the polybrene-treated group (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During the resultant regeneration phase the liver can be efficiently transduced with retroviral vectors, achieving hepatocyte transduction efficiencies of up to 35% following a single injection of vector. [9][10][11][12] Unfortunately, PH is a clinically unacceptable technique. Another approach has been to occlude a branch of the portal vein.…”
Section: Introductionmentioning
confidence: 99%
“…This enabled a four-fold increase in the in vivo transduction efficiency of the post-hepatectomy liver. 12 In this study we combined the administration of two growth factors with disparate intracellular mechanisms to induce hepatocyte proliferation in the intact liver and enable transduction with the amphotropic virus vector TELCeB/AF-7 21 complexed with the cationic liposome DOGS.…”
Section: Introductionmentioning
confidence: 99%
“…Virus containing supernatants were titred after filtration (0.8 m filters; Sartorius, Epsom, UK) in the presence of the polycation polybrene at 4 g/ml or the polyamine DOGS (dioctadecyl dimethyl ammonium chloride -Transfectam; Promega, Southampton, UK) at 5 g/ml as previously described. 21 Vector production under reduced serum conditions Virus producing WIL-E cells were grown at 6 × 10 6 cells/ml in RPMI 1640 medium or complete suspension medium (CSM -RPMI 1640 medium supplemented with 15% serum and 20% HL-1 medium) then transferred to medium with or without serum ( Figure 5). Supernatants were harvested after 18 h then titred on NIH3T3 cells.…”
Section: Introduction Of the Mfgnlslacz Vector Into Wil-2 Cellsmentioning
confidence: 99%